Analisis Faktor Advantageous Campaign, Relevant Content, Popular Content, Frequently Update Content, Various Platform And Application Terhadap Brand Loyalty Pada Bonolo.id - Dedi Setiadi; Yusi Tyroni Mursityo; Admaja Dwi Herlambang (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Bonolo using social media as one of the marketing tools. Instagram is selected because it has a large number of users and is mostly used for the purposes of buying and selling online. This research was conducted to find out the influence of social media marketing towards brand loyalty on social media account Instagram bonolo.id. In this study, which became population research is a customer account that follows bonolo Instagram bonolo.id and have already purchased the product. Data collection is done using the method of purposive sampling to 429 prospective respondents, where 110 of whom fill out questionnaires that are given. 10 the respondent eliminated from the final data because it does not meet the criteria of research respondents. The data collected was then analysed using multiple linear regression. Data analysis was done with the help of SPSS statistical software. The results of this study indicate that a variable advantageous campaign, popular content, and frequently update the content has an impact on the dependent variable is brand loyalty, it significantly. While variables relevant content and various platform and application do not have influence on the dependent variable significantly to brand loyalty.